Coleridge's "Dejection" : The Earliest Manuscripts and the Earliest Printings - Parrish, Stephen Maxfield (Cornell University Press, 2019)
This book offers a history of Coleridge's great Dejection poems, and presents the earliest manuscripts and earliest printed versions of these poems, along with the only known manuscript of another poem of Coleridge's, "The Day-Dream."In his introduction, Stephen Parrish traces the early development of the Dejection poems from their genesis in Coleridge's unhappy personal situation through the circumstances of their composition and revision. Reading texts of the recently discovered version of "Letter" and "The Day-Dream" are presented here for the first time, together with reading texts of a transitional version of "Letter," the October 1802 and 1817 published versions of "Dejection," and the only version of "The Day-Dream" published by Coleridge. The volume also contains photographs and transcripts of the principal manuscripts. Where appropriate, a record of variants is provided in the form of an apparatus.
Keywords: Coleridge, Samuel Taylor, -- 1772-1834. -- Dejection -- Criticism, Textual.; Coleridge, Samuel Taylor, -- 1772-1834 -- Manuscripts -- Facsimiles.; Coleridge, Samuel Taylor, -- 1772-1834; Dejection (Coleridge, Samuel Taylor); Manuscripts, English -- Facsimiles.; Musical Arts & Ethnomusicology.; Manuscrits anglais -- Fac-similés.; BIOGRAPHY & AUTOBIOGRAPHY / Composers & Musicians.; Manuscripts, English; Electronic books.; Criticism, interpretation, etc.; Facsimiles; Manuscripts